Women in the Extreme and Radical Right: Forms of Participation and Their Implications - Kristy Campion (Social Sciences, 2020)
The recent inclusion of male supremacy under the umbrella of right-wing extremism (RWE) can obscure the allure that the extreme and radical right holds for some women. This study examines women’s participation in the extreme and radical right to advance a novel conceptualization for engagement. Accordingly, six forms of participation are proposed, being violent actors, thinkers, facilitators, promoters, activists, and as gendered exemplars for others. This has implications for operations, ideology, and identity. First, women’s participation in violence has commonly been in conjunction with a group or a two-person dyad; it is rare that they operate as lone actors. Women also facilitate or sustain violent operations, through engaging in support activities that contribute to mission completion. Second, women create and promote radical right-wing ideology, challenge select discourses and magnify others to cultivate ideologically symbolic expressions of femininity. Third, such expressions contribute to extreme and radical belief systems, and provides select women with identity security and personal meaning. It is therefore possible to observe an ideological ecosystem spanning the extreme and radical right, in which women participate and interact.